تأثير استيعاب مادة المطالعة لمهارة الكلام - Eko Bowo Wicaksono; Alfy Mamduh Nuruddin (Fakultas Tarbiyah Universitas Ibrahimy, 2021)
The research aims to: (1) Determine the ability of class 3 students Intensive KMI Gontor Campus 2 in mastery of the Muthala'ah Uslub (2) Knowing the ability of Class 3 students Intensive KMI Gontor Campus 2 in speaking ability (3) Knowing whether there is an influence ability in mastery of Uslub Muthala'ah on the speaking ability of grade 3 students Intensive Kulliyatul Mu'allimin Al-Islamiyah Pondok Modern Darussalam Gontor Campus 2 Siman Madusari Ponorogo, East Java Academic Year: 1440 - 1441 H. This research applied quantitative method. The data collection technique used are (1) Test results, to know the ability of students in class 3 intensive KMI Gontor campus 2 in speaking skill. (2) Documentations, to get data on the value of learning achievement in muthola'ah lessons and the general description about the institutions. The data analysis used product moment correlation with a significance level of 5% or 1% with 73 degrees of freedom (df) 73. According to the analysis, it reveals that (1) mastery of muthola'ah grade 3 students Intensive KMI Gontor campus 2 school year: 1440-1441 is good with a grade of 5.58. (2) speaking ability of students in Intensive Class 3 KMI Gontor campus 2 academic year: 1440-1441 is very good with a score of 7.01. (3) There is a significant influence between mastery of muthola'ah and the speaking ability of grade 3 students Intensive KMI Gontor campus 2 academic year: 1440-1441, this was indicated by a value of 0.851 which was greater than the value of